Serotonin-induced hyperpolarization of an indentified Aplysia neuron is mediated by cyclic AMP. - Drummond, A H (1980)
Addition of serotonin to the medium bathing an Aplysia abdominal ganglion causes a change in the endogenous bursting activity of the identified neuron R15. At serotonin concentrations in the micromolar range, the predominant effect is an increase in depth and duration of the interburst hyperpolarization and consequent decrease in burst rate. At higher concentrations (10 microM) serototin can inhibit bursting completely. We have shown previously that these changes can be mimicked by bath application or intracellular injection of several cyclic AMP analogs substituted at the 8 position. Voltage clamp analysis indicates that serotonin and cyclic AMP analogs both cause an increase in membrane slope conductance in R15, with reversal potentials for the responses between -75 and -80 mV, close to the K+ equilibrium potential. When the K+ concentration in the bathing medium is changed, the reversal potentials change in a manner suggesting that serotonin and cyclic AMP analogs on K+ conductance are not additive. Furthermore, the effects of low concentrations of serotonin can be potentiated by the phosphodiesterase inhibitor Ro 20-1724. A pharmacological analysis indicates that the serotonin receptor that mediates hyperpolarization in R15 is similar to the serotonin receptor that we have shown to be coupled to adenylate cyclase. The present electrophysiological and pharmacological observations, together with our previous biochemical and pharmacological results, demonstrate that the serotonin-induced hyperpolarization of neuron R15 is mediated by cyclic AMP.